Weighted arithmetic average operator based on interval-valued intuitionistic fuzzy values and their application to multi criteria decision making for investment. Issue 2 (3rd March 2016) - Sudharsan, S.; Ezhilmaran, D.
Abstract: In this paper, we present aweighted arithmetic average operator based on intervalvalued intuitionistic fuzzy values and their application to multi criteria decision making for investment. Based on the scoring value method of interval-valued intuitionistic fuzzy values of the decision-maker with respect to alternatives